Somewhere in the darkness eaudiobook - Myers, Walter Dean (Recorded Books Inc., 2014)
An exciting, eye-catching repackage of acclaimed author Walter Dean Myers' bestselling paperbacks, to coincide with the publication of SUNRISE OVER FALLUJA in hardcover. Jimmy hasn't seen his father in nine years. But one day he comes back — on the run from the law. Together, the two of them travel across the country — where Jimmy's dad will find the man who can exonerate him of the crime for which he was convicted. Along the way, Jimmy discovers a lot about his father and himself — and that while things can't always be fixed, sometimes they can be understood and forgiven.